Sex estimation model for asian based on random forest using length of left hand bone - Mohd. Faaizie, Darmawan; Mohd Zamri, Ibrahim; Nasien, Dewi (Institute of Electrical and Electronics Engineers Inc., 2021)
Sex estimation is used in forensic anthropology to assist in the identification of human remains. The estimation model, on the other hand, is usually one-of-a-kind and only applies to a specific group of people. In addition, the study on Asian population also limited. This paper proposed sex estimation model using Random Forest based on the length of bones in x-ray images of left hand taken from Asian dataset. All the nineteen bones of the hand were appraised in centimeter using free image software and the Random Forest model was performed using Matlab. The result shows that the Random Forest model produced the best average of accuracy percentage on age group 16 to 18 years old which is 91.67% compare to the other group. The result also reveals that only this age group can be used for sex estimation due to the results produced more than 80%. However, due to the limited sample size, this study may not precisely reflect the overall Asian population, which it may impact the data's interpretation.